2008
DOI: 10.1590/s1519-566x2008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que afetam a oviposição de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) em pimentão

Abstract: -Bemisia tabaci (Gen.) biotype B is considered a pest of economical importance for several vegetables. The oviposition behaviour of the whilefl y was evaluated in sweet pepper plants. The trials were carried out under greenhouse condition and in the Laboratory of Entomology of DEFERS/ UNESP, Campus of Ilha Solteira-SP, with the sweet pepper Magali-R genotype. The effect of plant age on the whitefl y oviposition was evaluated in free-choice tests, in plants, 25, 30, 35, 40 and 45-day-old, as egg distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Our results agree with those of Lu et al [57] but differ from those of López et al [62], who indicated that the host plant did not influence the ability to generate offspring. In addition, this ability could depend on other factors such as the age of the plant, the position of the leaves within the foliage [63], or the quality of the foliage and its chemical composition [64]. However, these parameters were not measured in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Our results agree with those of Lu et al [57] but differ from those of López et al [62], who indicated that the host plant did not influence the ability to generate offspring. In addition, this ability could depend on other factors such as the age of the plant, the position of the leaves within the foliage [63], or the quality of the foliage and its chemical composition [64]. However, these parameters were not measured in our study.…”
Section: Discussionmentioning
confidence: 86%
“…It also has higher oviposition and feeding rates, and produces larger quantities of honeydew, in addition to inducing physiological disorders in infested plants (Perring 2001, Lima & Campos 2008.…”
Section: Introduc Onmentioning
confidence: 99%
“…Several studies report the importance of this pest species in other crops, such as beans, courgettes, okras, sweet peppers, tomatoes and watermelons (Lima & Campos 2008, Oriani et al 2008, Baldin et al 2009, Coelho et al 2009, Silva et al 2009. For soybean, the main damage stems from virus transmission, which is characterised by severe nanism, leaf curling, intense chlorosis and reduced seed production (Valle & Lourenção 2002).…”
Section: Introduc Onmentioning
confidence: 99%